Effect of Frontline Demonstrations on Production, Productivity and Profitability of Chickpea (Cicer arietinum) under Saline Conditions of Rajasthan's Agro-climatic Zone IIa.: Effect of frontline demonstrations on production of chickpea - Choudhary, Dr. Hari Ram; Singh, Dr. Gopichand; Sharma, Bhawana (Journal of Soil Salinity and Water Quality, 2023)
Cluster Front Line Demonstrations (CFLDs) are novel approaches that provides a direct interface between researchers and farmers by involving scientists directly in the planning, execution, and monitoring of demonstrations for technologies developed by them and receiving direct feedback from farmers in the field about the crops. The cluster frontline demonstrations were conducted on chickpea crop at Bijathal and That village of Riyabadi block under Krishi Vigyan Kendra, Athiyasan, Nagaur-I during rabi seasons of 2020-21 and 2021-22 held. Total number of 50 CFLDs in 20 ha area were planned with the aim of showcasing the improved production technologies designed to establish the crop's potential productivity. The improved technologies package consisting use of improved variety (GNG-2144), soil treatment by Trichoderma viride, seed treatment with Carbendazim, mechanized sowing, integrated nutrients application, weed management, disease and pest management by Tebuconazole and Emamectin benzoate were compared with farmers’ practices. Results revealed that the average yield of chickpea was observed as 1843 kg ha-1 in demonstration plots having improved variety as compared to local check (1460 kg per ha) which revealed 26.18% higher yield with incremental benefit: cost ratio of 0.90. The average technology gap, extension gap and technological index were found as 458 kg per ha and 19.89 percent, respectively. The results clearly indicate the positive effect of CFLDs over the existing practices to bridging the chickpea yield gap in saline soils.